13 CO/C 18 O gradients across the disks of nearby spiral galaxies - Jiménez-Donaire, Maria Jesús; Cormier, Diane; Bigiel, Frank (Arxiv, 2017)
We use the IRAM Large Program EMPIRE and new high-resolution ALMA data to measure 13CO(1-0)/C18O(1-0) intensity ratios across nine nearby spiral galaxies. These isotopologues of CO are typically optically thin across most of the area in galaxy disks, and this ratio allows us to gauge their relative abundance due to chemistry or stellar nucleosynthesis effects. Resolved 13CO/C18O gradients across normal galaxies have been rare due to the faintness of these lines. We find a mean 13CO/C18O ratio of 6.0$±$0.9 for the central regions of our galaxies. This agrees well with results in the Milky Way, but differs from results for starburst galaxies (3.4$±$0.9) and ultraluminous infrared galaxies (1.1$±$0.4). In our sample, the 13CO/C18O ratio consistently increases with increasing galactocentric radius and decreases with increasing star formation rate surface density. These trends qualitatively agree with expectations for carbon and oxygen isotopic abundance variations due to stellar nucleosynthesis, with a possible effect of fractionation.
Im Titel sind die Zahlen "13" und "18" hochgestellt
13CO/C18O gradients across the disks of nearby spiral galaxies
Gesehen am 25.10.2017